Transmission Dynamics of Carbapenem-Resistant Klebsiella pneumoniae Sequence Type 11 Strains Carrying Capsular Loci KL64 and rmpA/rmpA2 Genes - Kong, Yingying; Sun, Qingyang; Chen, Hangfei; Draz, Mohamed S.; Xie, Xinyou; Zhang, Jun; Ruan, Zhi (Frontiers in Microbiology, 2021)
The presence and dissemination of carbapenem-resistant Klebsiella pneumoniae (CRKP) often cause life-threatening infections worldwide, but the therapeutic option is limited. In this study, whole-genome sequencing (WGS) was applied to assess the epidemiological characteristics and transmission events of CRKP isolates in two fetal outbreaks of nosocomial infection. Between April 2016 and March 2018, a total of 70 isolates of K. pneumoniae were collected from sterile samples in a tertiary hospital in Hangzhou, China. The minimal inhibitory concentrations (MICs) of 21 antimicrobial agents were determined using the broth microdilution methods. Pulsed-field gel electrophoresis (PFGE) was performed on 47 CRKP isolates, and 16 clonally related isolates were further characterized by Illumina sequencing. In addition, the complete genome sequences of three representative isolates (KP12, KP36, and KP37) were determined by Oxford Nanopore sequencing. The K. pneumoniae isolates were recovered from patients diagnosed with pulmonary infection, cancer, or encephalopathy. For all CRKP isolates, PFGE separated three clusters among all strains. The most predominant PFGE cluster contained 16 isolates collected from patients who shared close hospital units and represented a potential outbreak. All 16 isolates showed an extremely high resistance level (≥ 87.5%) to 18 antimicrobials tested but remain susceptible to colistin. Multiple antimicrobial resistance and virulence determinants, such as the carbapenem resistance gene blaKPC-2, and genes encoding the virulence factor aerobactin and the regulator of the mucoid phenotype (rmpA and rmpA2), were observed in the 16 CRKP isolates. These isolates belonged to sequence type 11 (ST11) and capsular serotype KL64. A core genome single nucleotide polymorphism (cgSNP) based phylogenetic analysis indicated that the 16 CRKP isolates could be partitioned into two separate clades (≤ 15 SNPs), suggesting the two independent transmission scenarios co-occurred. Moreover, a high prevalence of IncFIB/IncHI1B type virulence plasmid with the iroBCDN locus deleted, and an IncFII/IncR type blaKPC-2-bearing plasmid was co-harbored in ST11-KL64 CRKP isolates. In conclusion, our data indicated that the nosocomial dissemination of ST11-KL64 CRKP clone is a potential threat to anti-infective therapy. The development of novel strategies for surveillance, diagnosis, and treatment of this high-risk CRKP clone is urgently needed.